Social media for strategic communication : creative strategies and research based applications / Karen Freberg, University of Louisville. - Freberg, Karen June
Social Media for Strategic Communication: Creative Strategies and Research-Based Applications Second Edition teaches students the skills and principles needed to use social media in persuasive communication campaigns. This book combines cutting edge research with practical, on-the-ground instruction to prepare students for the real-world challenges they'll face in the workplace. By focusing on strategic thinking and awareness, this book gives students the tools they need to adapt what they learn to new platforms and technologies that may emerge in the future. A broad focus on strategic communication - from PR, advertising, and marketing, to non-profit advocacy-gives students a broad base of knowledge that will serve them wherever their careers may lead. The Second Edition features new case studies and exercises and increased coverage of diversity and inclusion issues and influencer marketing trends. Features and Benefits: A Broad Focus on Strategic Communication reflects a larger, discipline-wide trend toward integrated marketing communications An Emphasis on Strategies and Tactics gives students the skills they need to be able to apply their knowledge across various platforms and on to new, yet-to-be-be-developed technologies Profiles with Key Experts show students how social media is used in real-world settings Chapter-Opening Case Studies emphasize how social media fits in to a larger strategic communications campaign